Clitoral reconstruction and psychosexual care after female genital mutilation/cutting: Assessment of multidisciplinary care - Muriel Meyer; Gideon Sartorius; Jasmine Abdulcadir (Women's Health)
Background: Multidisciplinary care following female genital mutilation/cutting (FGM/C) can consist of surgical interventions such as clitoral reconstruction (CR) in combination with individualized psychosexual care (PC). Evidence on both treatments, alone or in association, is limited. Objectives: To investigate the overall satisfaction with PC only or PC in combination with CR. Design: Cross-sectional study of women who attended the FGM/C outpatient clinic under study and asked for CR between January 2013 and November 2021. Methods: Data were collected through questionnaire-based interviews on motivations for asking for CR, psychological well-being (World Health Organization-Five Well-Being Index), sexual response (Female Sexual Function Index), vulvar pain, genital self-image (Female Genital Self-Image Scale), overall satisfaction with the care received, and, in the case of CR, postoperative complications. Results: The 20 women included underwent therapy primarily to feel repaired or reconstructed and to improve their sexual function. Mean overall satisfaction with the care was rated 8.95/10 ± 1.39. Twelve (60%) received CR in combination with PC. Eight (40%) received PC only. Women who received combined therapy reported higher overall satisfaction (9.17 versus 8.57), psychological well-being (17.8 versus 9.25), sexual response (31.22 versus 21.56), and genital self-image (25.60 versus 17.60) in comparison with those who only received PC. The main surgical complications were minor postoperative bleeding and one painful wound infection triggering a relapse of posttraumatic stress disorder. Conclusion: Tailored PC and CR after FGM/C seem to improve psychosexual health, well-being, body image, and pain. Registration: ClinicalTrials.gov (NCT05026814)